AN ANALYSIS OF STUDENTS’ WRITING SKILLS: FOCUS ON GRAMMATICAL AND DISCOURSE COMPETENCE - Hadiani, Dini (LLT Journal: A Journal on Language and Language Teaching, 2019)
This paper presents an analysis of the students? writing skills. It is believed that writing is a powerful device to reflect language structure and to promote language learning.  However, many students still experience difficulties in writing since it requires the appropriate grammatical and textual structures. Therefore, this study tries to analyse the students? writing skills that will help them to improve their communicative competence. Data were obtained through documentation of students? texts and interviews. The theories of Systemic Functional Linguistics, explanation text, and communicative competence were employed as the framework of the text analysis. The findings revealed the social function, the generic structure, the linguistic features, and also the grammatical and discourse competence in students? explanation texts. It was concluded that the students perceived the importance of the use of correct grammar and textual structure in their writing. Regarding some grammatical mistakes in students? explanation texts, it is recommended that teacher give explicit teaching and more exercises to them so that the students? communicative competence can be developed.DOI: 10.24071/llt.2019.220206